1991
DOI: 10.1007/bf02493486
|View full text |Cite
|
Sign up to set email alerts
|

Using ventilators for speaking and swallowing

Abstract: An inflated cuff, although commonly thought to be required for the ventilator-dependent patient with a tracheostomy cannula, precludes speaking and has adverse implications for swallowing. Clinical trials with five ventilator-dependent, cognitively intact individuals with glottic control document that a deflated cuff is compatible with ventilation, preserves oral communication, and restores safe alimentation by mouth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Several approaches to eliminating or reducing aspiration in this patient population have been discussed in the literature. Some have reported that deflating the tracheostomy cuff improves swallow function [13]. To date, no research has examined the effect of cuff deflation on specific aspects of swallowing physiology, such as hyolaryngeal excursion or cricopharyngeal opening.…”
mentioning
confidence: 99%
“…Several approaches to eliminating or reducing aspiration in this patient population have been discussed in the literature. Some have reported that deflating the tracheostomy cuff improves swallow function [13]. To date, no research has examined the effect of cuff deflation on specific aspects of swallowing physiology, such as hyolaryngeal excursion or cricopharyngeal opening.…”
mentioning
confidence: 99%
“…Some have suggested that the presence of an inflated tracheotomy tube cuff adversely affects swallowing. 13,23,24 Although not supported by empirical data, an inflated cuff was conjectured to either tether the larynx and reduce hyolaryngeal excursion and airway closure during the swallow or impinge on the tracheoesophageal wall and impede the passage of food or liquid through the esophagus. 6,13 Tippett and Siebens 24 examined the effects of tracheotomy tube cuff deflation on swallowing in 5 ventilator-dependent individuals, aged 21 to 70 years.…”
Section: Cuff Deflation and Swallowingmentioning
confidence: 97%
“…Ventilation can be adequately maintained during cuff deflation in most individuals, despite some leakage of air through the larynx during inspiration. [68][69][70] Initially, to build tolerance for cuff deflation, it may be helpful to adjust ventilator settings such as tidal volume and to learn to volitionally close the glottis as needed to direct all inspired air to the lungs. By having the cuff partially or fully deflated, it is possible to produce "leak speech" by allowing a small amount of air to reach the vocal folds.…”
Section: Invasive Ventilationmentioning
confidence: 99%